2023
DOI: 10.1136/bmjgh-2022-010942
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for anti-hyperglycaemic medication for type 2 diabetes mellitus in China: findings from a national survey

Abstract: ObjectiveThis study aimed to investigate the preferences regarding risks, benefits and other treatment attributes of patients with type 2 diabetes mellitus (T2DM) in China when selecting a second-line anti-hyperglycaemic medicine.MethodsA discrete choice experiment with hypothetical anti-hyperglycaemic medication profiles was performed using a face-to-face survey administered to patients with T2DM. The medication profile was described using seven attributes: treatment efficacy, hypoglycaemia risk, cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Our literature review on DCEs for drug treatment preferences revealed that these attributes commonly encompass outcome (e.g., efficacy and adverse effects), process (e.g., mode of administration) and cost. 9 , 10 , 14 , 15 , 16 , 17 , 18 Additionally, we conducted a literature review to gain insights into the characteristics of lipid‐lowering drugs, and the search strategy can be found in Supporting Information S1: Appendix 1 . Thus, we identified 10 candidate attributes based on the literature review (Supporting Information S1: Appendix 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our literature review on DCEs for drug treatment preferences revealed that these attributes commonly encompass outcome (e.g., efficacy and adverse effects), process (e.g., mode of administration) and cost. 9 , 10 , 14 , 15 , 16 , 17 , 18 Additionally, we conducted a literature review to gain insights into the characteristics of lipid‐lowering drugs, and the search strategy can be found in Supporting Information S1: Appendix 1 . Thus, we identified 10 candidate attributes based on the literature review (Supporting Information S1: Appendix 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Discrete choice experiment (DCE) is a quantitative approach which is used to elicit individual preferences through trade‐offs among alternatives. 13 It has gained popularity for quantifying preferences in drug therapy, including cancer treatment, 9 , 14 antiepileptic drugs, 10 antihyperglycemic medications, 15 asthma medications, 16 treatments for rheumatoid arthritis 17 and anticoagulant therapy. 18 These DCE studies have provided insights into the preferences of respondents for treatment options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation